2020
DOI: 10.1021/acs.jafc.0c02101
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Tryptanthrins as Novel Antiviral and Anti-Phytopathogenic-Fungus Agents

Abstract: Plant diseases seriously affect the yield and quality of crops and are difficult to control. Tryptanthrin and its derivatives (tryptanthrins) were synthesized and evaluated for their antiviral activities and fungicidal activities. We found that tryptanthrins have good antiviral activities against tobacco mosaic virus (TMV) for the first time. Most of the tryptanthrins showed higher anti-TMV activities than that of ribavirin (inhibitory rates of 40, 37, and 38% at 500 μg/mL for inactivation, curative, and prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 24 publications
0
38
0
Order By: Relevance
“…For the substitution on the aromatic ring of position R 2 , hydroxy group is beneficial for the antiviral activity, and the electron-withdrawing groups at the same position benefit the antiviral activity. Hao et al also found that the substitution by an electron-withdrawing group improved the biological activity of tryptanthrin derivatives …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the substitution on the aromatic ring of position R 2 , hydroxy group is beneficial for the antiviral activity, and the electron-withdrawing groups at the same position benefit the antiviral activity. Hao et al also found that the substitution by an electron-withdrawing group improved the biological activity of tryptanthrin derivatives …”
Section: Resultsmentioning
confidence: 99%
“…Hao et al also found that the substitution by an electron-withdrawing group improved the biological activity of tryptanthrin derivatives. 36 3.4. Effects of Compounds 5 and 11 on Root Length, Bud Length, Dry Weight, and Phytotoxic Activity of N. benthamiana.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 7 aa can be oxidized to obtain alkaloid tryptanthrin ( 8 aa ). Its antiviral activities have been studied recently [15] . The carbonyl group and C−N bond of 7 aa can be selectively reduced by employing B(C 6 F 5 ) 3 and NH 3 ‐BH 3 to generate the indoline product 9 aa .…”
Section: Resultsmentioning
confidence: 99%
“…A majority of substituted quinazoline derivatives are known for their broad-spectrum biological activities including anticancer (tyrosine kinase inhibitors), antiviral, anti-inflammatory, antiprotozoan, antifungal, antibacterial, diuretics, antimalarial, antidepressant, muscle relaxants, antitubercular, anticonvulsant and many more. [1][2][3][4][5][6][7][8][9][10][11][12] Among the 4-substituted quinazolines, 4-amino and 4-phenoxy derivatives have been known to constitute an active class of drugs [13] and other materials, [14] while on the other hand, the 4-carbonyl derivatives of quinazoline such as quinazolin-4-carboxamides have not explored well so far despite exhibiting variety of biological properties such as potent inhibitor of AAKl, acetyl CoA carboxylase inhibitor, anti-disorders, adenosine receptors, anti-neurodegenerative, and anticancer have been described (Figure 1). [15][16][17][18][19][20] In the past few decades, the catalytic one-pot multicomponent reactions has become a powerful tool for the synthesis of N-containing biologically active heterocycles.…”
Section: Introductionmentioning
confidence: 99%